Effect of the Booming Tilapia Cage Culture on The Water Quality in Selected Bays of The Bukavu Basin, Lake Kivu, Democratic Republic of The Congo - Gabriel Balagizi Baguma; Christine Cocquyt; Venant Muderhwa Nshombo; Alfred Kabagale Cubaka; Alicet BwanaMudogo Irenge; Nelly Furaha Nakangu; Jean-Claude Balungwe Kadjunga; Désiré Balagizi Akonkwa; Mulongaibalu Mbalassa (Journal of Aquaculture Science, 2024)
This study aimed to assess the impact of the Nile Tilapia (Oreochromis niloticus) cage fish farming on the water quality in two selected bays of the Bukavu basin, Lake Kivu. Physicochemical parameters (pH, temperature, electrical conductivity, total dissolved solids, salinity, dissolved oxygen, transparency) were measured in situ using a COMBO HI 98129 multi-parameter probe, PCE-PHD1 probe, and a Black and White Secchi disk. Water samples at different depths were collected using a Van-Dorn Sampler and phosphate, ammonia, nitrite, silicate, and chlorophyll-a were analyzed using a UV-VIS spectrophotometer. The results revealed that the pH, temperature, total dissolved solids, salinity, and transparency were significantly different (p ≤ 0.05) between the bays with cages and at the control bay, which may be due to the low movement of water, and the density of fish inside the cages. The water nutrients such as phosphate, ammonia, nitrite, silicate, and primary productivity were significantly different (p ≤ 0.05) within the bays with cages than at the control bay without cages. Overall, the results demonstrate that Tilapia cage culture contributes to the deterioration of water quality parameters accelerating the eutrophication process in Bukavu basin, Lake Kivu. Therefore, the study recommends relocating the cages to the bays not impacted by the anthropogenic activities from the catchment and regulating fish feeding according to the bioavailability of nutrients in the bays.